Quantifying the relationships between soil fraction mass, fraction carbon, and total soil carbon to assess mechanisms of physical protection. (August 2019) - King, Alison E.; Congreves, Katelyn A.; Deen, Bill; Dunfield, Kari E.; Voroney, R. Paul; Wagner-Riddle, Claudia
Abstract: Relationships between soil fractions (their mass or carbon (C)) and soil organic carbon (SOC) have been used to develop central ideas in SOC research. However, few attempts have been made to quantify the relationship between SOC and all soil fractions, despite the potential for such an effort to address SOC stabilization processes. We identified 41 published studies that used diverse management techniques to cause a change in SOC concentration and disrupted soil into macroaggregates (>250 μm), free microaggregates (53–250 μm) and free silt + clay (<53 μm), subsequently disrupting macroaggregates into constituent fractions (coarse particulate organic matter [cPOM] > 250 μm, occluded microaggregates, and occluded silt + clay). We used linear hierarchical models to quantify relationships between mass, C concentration and total C of fractions and SOC. Soil mass redistribution toward macroaggregates was associated with SOC accumulation, however total microaggregate mass (free + occluded) did not increase with macroaggregate mass, as would be expected given de novo microaggregate formation within macroaggregates. Instead, high SOC soils exhibited a greater percent of total microaggregates occluded in macroaggregates. Occlusion in macroaggregates was also associated with increased C concentrations of microaggregates (35% higher, SE = 3.2) and silt + clay (30% higher, SE = 3.9) relative to their free counterparts. Taken together, these relationships suggest reduced macroaggregate turnover promotes SOC accumulation via the stabilization of C into occluded fractions. Rates of SOC increase with silt + clay C concentrations failed to increase with mean site-level SOC concentration, indicating of the studied soils (median SOC concentration = 14 g kg −1 ; max 68), SOC accumulation appears unlikely to be limited by C storage capacity in the silt + clay fraction. For each unit SOC gain, macroaggregates accounted for 83% (95% CI = 74, 91), and occluded microaggregates for 43% (95% CI = 33, 52), consistent relationships that have potential to be used as benchmarks for fraction-based SOC models. Graphical abstract: Image 1 Highlights: We quantitatively reviewed 41 studies reporting macroaggregate-occluded fractions. SOC increase was associated with gains in macroaggregate mass. Macroaggregate-occlusion increased C concentration of microaggregates, silt + clay. Macroaggregates may enable stabilization of POM to microaggregates, silt + clay. 83% of SOC accumulated in macroaggregates; 43% occurred in occluded microaggregates.